Moçambique - recessão antes do boom: Reflexões sobre picos de investimento e novas fontes de gás - Roe, Alan (2018)
Este artigo surge na sequência de um artigo anterior onde se considerou em termos gerais muitas das questões que Moçambique enfrenta hoje em dia na gestão dos seus novos recursos extractivos. Em primeiro lugar descreve-se o pico de investimento já desencadeado pelas novas descobertas de gás em Moçambique. Depois apresenta-se em resumo alguma da literatura mais recente sobre os efeitos desses picos noutros países e contextos. De seguida analisam-se os principais aspectos dos resultados económicos decepcionantes testemunhados até 2018, e analisase selectivamente algumas das implicações destes resultados nas políticas futuras. O artigo conclui explorando a epidemiologia de um grande pico do investimento público — uma questão que tem relevância para o pico adicional que ainda é esperado. Ao seguir esta sequência de argumento, procura-se igualmente compreender melhor diversas questões fundamentais de política geral que surgem no contexto das grandes descobertas de novos recursos.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Mozambique - bust before boom: Reflections on investment surges and new gas - Roe, Alan R. (WIDER Working Paper Series, 2018)
This paper is a sequel to an earlier paper that looked in broad terms at many of the issues that Mozambique faces today in managing its new extractive resources. The paper first describes the investment surge that has already been prompted by new gas discoveries in Mozambique. It then summarizes some of the more recent literature that has examined the effects of such surges in other country contexts. It next examines the main aspects of the disappointing economic outcomes that have so far been seen through 2018, and selectively analyses some of the implications of these outcomes for future policy. The paper concludes by exploring the epidemiology of a large public investment surge—an issue that has relevance for the further surge that is still anticipated. In following this sequence of argument, the paper also throws light on a number of critical general policy questions that arise in the context of major new resource discovery.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

Mozambique plantation leaves no land or jobs for villagers - Adler, Nils (New Internationalist, 2018)
In northern Mozambique, villagers were promised jobs to replace land taken for forestry. Five years later, they’re still waiting, discovers Nils Adler.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Extractives and economic diversification in Mozambique: will local content do the trick? (Research Brief 2/2018, 2018)
Research Findings - It is unlikely that the extractives sector can any time soon be used to finance visionary transformation strategies aimed at achieving economic diversification. Due to the country’s fiscal situation and delays in developing the offshore natural gas sector, it seems that extractives will not provide additional revenues for at least another decade, if not longer. If the fiscal crisis results in the further deterioration of the provision of public goods and services, the business environment will become worse for the country’s micro, small and medium-sized enterprises. There is the risk that the gap will widen even further between the skills and entrepreneurial capabilities available in the country, and those required by foreign investment projects and their supply chains. Such a prospect does not match well with the expectations that local content policies can provide the silver bullet for diversifying the economy.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector / setor privado